The role of prototypes in communication between stakeholders - Lauff, Carlye A.; Knight, Daniel; Kotys-Schwartz, Daria; Rentschler, Mark E. (Design studies, 2020)
Prototypes are complex and dynamic artifacts that shape social situations during product development. A ten-month applied ethnographic study of a footwear company recounts prototypes' evolving role in communication between three stakeholder groups. In this case study, we use Mol's “bodies multiple” theory to describe prototypes enactment as communication tools across contexts. This study finds that prototypes become encoded with information that is translated, decoded, and re-encoded by stakeholder groups. Prototypes remain the same across contexts, yet the spokesperson guiding the prototype may change. Raising awareness of prototypes role in communication, such as their ability to build confidence through socialization, can allow design teams to better plan for how information is encoded into the prototyped artifact and the messaging surrounding it. •Applied ethnographic study of a footwear company developing a new boot.•Prototypes are communication tools to explain, gain feedback, negotiate, or persuade.•Knowledge is embodied in prototypes and translated across contexts.•Stakeholder interactions define the various project contexts.•Socialization occurs around prototypes as a means to build confidence in a project.